Spontaneous Resolution of Symptomatic Hepatic Sarcoidosis - Viva Nguyen; Henry N. Ngo; Hamza H. Awad (Case Reports in Gastrointestinal Medicine)
Sarcoidosis is an inflammatory process of unknown etiology, characterized by noncaseating granulomas. Isolated extrapulmonary disease is rare. We present a case of a 60-year-old woman with chronically elevated alkaline phosphatase. Upon obtaining a liver biopsy, granulomatous hepatitis was observed, suggestive of sarcoidosis. No particular treatment was initiated, and 3 years following the onset of elevated alkaline phosphatase, her levels decreased spontaneously.